Il problema dei limiti alla libertà religiosa alla prova della pandemia: specialità o privilegio? (a margine delle relazioni di Silvia Baldassarre, Simone Gianello e Paolo Zicchittu) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa: sui così detti limiti impliciti - 2. Le misure limitative della libertà religiosa alla prova dei test di bilanciamento - 3. Il ritorno della specialità (o del privilegio) nella seconda fase della pandemia.The problem of limits to religious freedom under the pandemic test: specialty or privilege? (about the reports by Silvia Baldassarre, Simone Gianello and Paolo Zicchittu)ABSTRACT: In this contribution, which takes its cue from the reports by Silvia Baldassarre, Simone Gianello and Paolo Zicchittu, the author makes some brief remarks on the subject of limits to religious freedom, the difficulties of balancing them, and the legitimacy of differential treatment between spiritually connoted activities.